2013
DOI: 10.3126/kumj.v10i2.7344
|View full text |Cite
|
Sign up to set email alerts
|

Perception About the Role of Anesthesia and Anesthesiologist Among the Paramedical Staffs: Perspective from a Medical College in Nepal

Abstract: BackgroundAnesthesiologists and anesthesia has been considered behind the scene. The image and status of anesthesiologist in the eyes of the medical and lay communities has always been a problem. ObjectivesThis study was designed to assess the knowledge about the role of anesthesiologist among the paramedical staffs at Kathmandu University Hospital. MethodsThis prospective questionnaire based study was done at Kathmandu University School of Medical Science, Dhulikhel Hospital for 2 nd January 2011 to 30 th Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 10 publications
2
20
1
Order By: Relevance
“…This study reveals that 80.6% of nurses had knowledge about complications and management of spinal anaesthesia which is similar to the study conducted at Dhulikhel hospital which reported 73.3% knew about the complications of regional anaesthesia 6 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This study reveals that 80.6% of nurses had knowledge about complications and management of spinal anaesthesia which is similar to the study conducted at Dhulikhel hospital which reported 73.3% knew about the complications of regional anaesthesia 6 .…”
Section: Discussionsupporting
confidence: 84%
“…An Intervention Study to Enhance Postoperative Pain Management in the nurses of anesthesia, and surgery departments identified a lack of knowledge and skills among nurses in assessing and managing pain effectively because of the absence of nursing guidelines and pain treatment protocols 5 . Similar study conducted at Kathmandu University School of Medical Science, Dhulikhel Hospital among paramedical staff shows that 26.7% had no idea about the complications 6 . Likewise, study conducted at Nepalgunj Teaching Hospital Kohalpur on nurses to assess the knowledge regarding SA found to be unsatisfactory and indicate the need of essential training on management of spinal anesthesia 7 .…”
Section: Introductionmentioning
confidence: 51%
“…However, for the management of postoperative complications, respondents put confidence mostly to surgeons, somewhat to other physician (77%, and 18% of respondents) with no mention of anaesthesiologists. 29 In the present survey, only 10% of the patients knew about the roles of anaesthesiologist outside the OR. Out of these, around 6% knew about duty in CCU and 3% were aware of role in pain management.…”
Section: Discussionmentioning
confidence: 58%
“…The lack of recognition can simply affect the selfesteem of the anaesthesiologists and help budding job dissatisfaction. 29 This will hamper the performance and thereby the output by the anaesthesiologists in the long run.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial amount of research has revealed poor awareness of anaesthesiology among doctors, interns, medical/dental students, and paramedics. 2,3,4 Studies have also revealed that medical students find anaesthesiology as uninteresting and less glamourous. 5 Thus, this study was conducted with the aim of finding out the awareness and knowledge of undergraduate medical students (Preclinical batches) regarding anaesthesiology as a speciality, as a career choice, different roles of Anaesthesiologists in operative rooms and hospital.…”
mentioning
confidence: 99%